2006
DOI: 10.3102/00346543076001063
|View full text |Cite
|
Sign up to set email alerts
|

Student Employment and Higher Education: Empiricism and Contradiction

Abstract: College student employment has been increasing steadily for at least four decades. At present, approximately 80% of all college students are employed while completing their undergraduate education. Even among students under the age of 24 at 4-year colleges, more than 50% are employed during the school year. Although some general trends are suggested by empirical research completed to date, studies that evaluate student employment and higher education are at times inconsistent and even contradictory. Despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 23 publications
5
133
0
15
Order By: Relevance
“…Concomitantly, researchers have become increasingly interested in studying the consequences of paid work during the college years. In an extensive review of empirical research about the relationship between paid work and college student academic performance and attrition, Riggert and his colleagues concluded that findings are inconsistent: some studies show positive relationships and others negative, and yet others non-significant relationships (Riggert et al 2006). For instance, Butler (2007) reports that the effects of paid work on college educational outcomes depend on job characteristics, with those jobs that are congruent in content with the major pursued and/or offering substantial control over work activities having a positive effect on academic outcomes, whereas other jobs with high burdens of work hours and demands exerting a negative influence on these outcomes.…”
Section: Empirical Evidence Regarding the Consequences Of Working Durmentioning
confidence: 99%
“…Concomitantly, researchers have become increasingly interested in studying the consequences of paid work during the college years. In an extensive review of empirical research about the relationship between paid work and college student academic performance and attrition, Riggert and his colleagues concluded that findings are inconsistent: some studies show positive relationships and others negative, and yet others non-significant relationships (Riggert et al 2006). For instance, Butler (2007) reports that the effects of paid work on college educational outcomes depend on job characteristics, with those jobs that are congruent in content with the major pursued and/or offering substantial control over work activities having a positive effect on academic outcomes, whereas other jobs with high burdens of work hours and demands exerting a negative influence on these outcomes.…”
Section: Empirical Evidence Regarding the Consequences Of Working Durmentioning
confidence: 99%
“…A pesar de la significativa extensión del fenómeno en muchos países, y de la relevancia del mismo para estudiantes, instituciones educativas y el conjunto de la sociedad, ciertas cuestiones relevantes, como la relación entre el desempeño de un trabajo y el rendimiento académico de los estudiantes universitarios han sido poco investigadas, con un número de estudios relativamente modesto de los cuales la inmensa mayoría tiene un carácter empírico. En consecuencia, aunque la literatura actual responde a algunas importantes cuestiones sobre los efectos del empleo de los estudiantes universitarios, existen importantes interrogantes abiertos (puede encontrarse una revisión exhaustiva reciente de los estudios sobre esta cuestión Riggert et al, 2006; para una revisión anterior de la literatura, véase Lyons, Krachenberg & Henke, 1986).…”
Section: La Relación Entre Trabajo Y Estudio Universitariounclassified
“…Así, mientras que algunos estudios sugieren que trabajar tiene un impacto perjudicial sobre el rendimiento (véanse, por ejemplo, Tyler, 2003;Stinebricker & Stinebricker, 2003, o Hawkings et al, 1995, otros apuntan a que el empleo tiene un impacto neutral o incluso beneficioso (Furr & Elling, 2000;Nonis y Hudson, 2006;Pascarella, Bohr, Amaury, Desler & Zusman, 1994, y Pascarella, Edison, Nora, Hagedorn & Terenzini, 1998Canabal;1998;Hammes & Haller, 1983, y Gleason, 1993, si bien es posible que un impacto negativo sea más evidente en el caso de jornadas laborales más extensas. En cualquier caso, cabe destacar que los efectos identificados son en todos los casos de pequeña magnitud.…”
Section: La Relación Entre Trabajo Y Estudio Universitariounclassified
See 2 more Smart Citations